Harmonization of Customary Inheritance System and National Law: A Study of Maqasid Sharia Perspective - Asrianti Sukirman; Oyo Sunaryo Mukhlas; Siah Khosyi'ah; Ahmad Hasan Ridwan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Indonesia, as a multicultural country, has three coexisting inheritance law systems: customary law, Islamic law (through the Compilation of Islamic Law/KHI), and civil law (Civil Code). These three systems often exhibit fundamental differences in terms of normative foundations, inheritance mechanisms, and the values of justice they uphold. Through a maqashid syariah approach emphasizing protection of religion (dīn), life (nafs), intellect (‘aql), lineage (nasl), property (māl), and justice (‘adl), this study analyzes the common ground and gaps between customary and national inheritance law. The analysis reveals that while customary law seeks to preserve property and social structures, discriminatory practices and inadequate protection for vulnerable groups still exist. Conversely, the KHI, as part of national law, is more systematic in ensuring distributive justice, though it remains rigid and requires contextualization. This study recommends the importance of normative reconstruction through the compilation of standardized national customary inheritance law based on the values of maqashid and Pancasila, as a step toward an inclusive, fair, and sustainable inheritance law system.